For the Good of the Field - Newton, Richard (Bulletin for the study of religion, 2020)
In this introduction to the newly relaunched the Bulletin for the Study of Religion, Dr. Richard Newton, the Bulletin’s new editor, provides a succinct overview of what this fresh take on one of the field’s earliest publicationshas to offer for a contemporary readership. While staying true to its roots and continuing to publish experimental pieces from scholars in the field, as well as classics taken from the publication’s archives, the Bulletin will now features a series of new, rotating columns that will cover everything from digital scholarship in the humanities to all the happenings at recent meetings of noteworthy conferences and events in the field.